Pengaruh Ekspor, Impor Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Indonesia - Nabila Nabila; Sulis Tia Wati; Yani Rizal; Puti Andiny; Safuridar Safuridar (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to determine the effect of exports, imports and government spending on national economic growth from 2009 to 2023. The data used in the study is secondary data sourced from the Central Statistics Agency (BPS) and the Ministry of Finance (Kemenkeu). The research employs a quantitative method through multiple linear regression, with the software Eviews 10 used for analysis. The results of the research indicate that, in part, exports exert a negative and significant influence on national economic growth, while imports exert a positive and significant influence. Furthermore, government expenditure exerts a negative and significant influence on national economic growth. These variables, exports, imports and government expenditure, exert a simultaneous influence on national economic growth.